Alkyliodines in High Oxidation State: Enhanced Synthetic Possibilities and Accelerated Catalyst Turn‐Over. Issue 60 (29th August 2019) - Bosnidou, Alexandra E.; Muñiz, Kilian
Abstract: In contrast to aryliodine(III) compounds, which have matured into a particularly attractive class of oxidants in modern synthesis, the synthetic potential of related alkyliodine(III) derivatives has remained widely underestimated. This is surprising since several unique synthetic possibilities arise directly from the low stability of their central carbon–iodine bond. In this respect, these high‐oxidation‐state iodine compounds resemble environmentally benign variants of the prominent metal counterparts such as those derived from palladium, nickel and copper. This Concept article summarizes the general reactivity trends in alkyliodine(III) chemistry and discusses selected examples of their strategic use as highly reactive, transient species in organic synthesis and homogeneous catalysis. Abstract : Broaden your horizons : Scant attention, but very versatile: alkyliodine(III) high‐oxidation‐state reagents offer multiple synthetic possibilities in synthesis and catalysis.